Cost-efficiency analysis of multiple ecosystem services across forest management regimes - Rana, Parvez; Juutinen, Artti; Eyvindson, Kyle; Tolvanen, Anne (Academic Press, 2024)
Forest management is at the crossroads of economic, environmental, and social goals, often requiring strategic trade-offs. As global demands surge, it's vital to employ management strategies fostering multifunctional landscapes, enabling ecosystem integrity while procuring resources. Historically, the boreal forest in Fennoscandia has been intensively managed for timber, causing environmental shifts and conflicts with biodiversity conservation and climate mitigation policies. Application of current management practices while increasing harvests are a threat to both biodiversity and carbon stocks. To explore this issue, we quantify the cost-efficiency of two forest management regimes: rotation forestry (RF) and continuous cover forestry (CCF), considering specific forest attributes like soil type (mineral and peat soils), site type (fertility classes) and tree stand age, which have been underexplored in previous research. We simulated 45,559 forest stands for 100 years in Northern boreal forests of Finland. We proposed two straightforward cost-efficiency indices (CEI) to evaluate the performance of these management regimes, specifically focusing on their impact on economic output, biodiversity conservation (measured as a biodiversity index for six forest vertebrates, including five bird species and one mammal) and carbon stock. Our findings suggest that continuous cover forestry holds the potential to deliver more cost-efficient ecosystem services and maintain greater biodiversity compared to rotation forestry approaches. Continuous cover forestry, however, is not optimal for all at management units, which calls for alternative management options depending on the stand characteristics. The cost-efficiency indices performance of rotation forestry and continuous cover forestry depend on the characteristics of the initial stand which is largely determined by the previous management of the stand. Our results contribute to guiding forest management towards enhanced sustainability and ecological balance. The great variation in stand characteristics suggest a need for diverse management strategies to create multifunctional landscapes. Our proposed cost-efficiency indices could serve as practical tools for decision-making.
Keywords: continuous cover forestry; biodiversity; ecosystem services; climate changes; cost-efficiency index